Model of the Road Capacity Influence on Traffic Congestion and Noise Disturbance on Wonocolo - Sepanjang Road at Sidoarjo Region - Pontoh, Enny Merry; Mudjanarko, Sri Wiwoho; Prasetijo, Joewono (LPPM of NAROTAMA UNIVERSITY, 2024)
Traffic congestion and noise are significant issues in rapidly developing urban areas. This study examines the impact of road capacity on congestion and noise levels starting from Wonocolo to Sepanjang road in Sidoarjo regency. The objectives are to analyze the road capacity, its influence on traffic congestion, and the correlation with noise pollution. Using the MKJI 1997 method, traffic and noise data were collected and analyzed during peak hours. The results indicate that increased road capacity has a direct effect on reducing congestion, but also influences noise levels. The findings suggest that managing road capacity effectively can mitigate traffic congestion and noise pollution. Contributing to a better urban planning and transportation management.